Determinação de açúcares totais em refrigerantes com smartphone - Schlesner, Sandra Kunde (2020)
The techniques commonly used for determination of sugar in non-alcoholic beverages are classical methods based on different physical and chemical principles. A common drawback of these methods is the long time for analysis, the consumption of a high amount of reagents and the generation of waste. In some cases, as for the official method for determination sugars in beverages (AOAC 923.09), the analytical procedure should be carried out under heating, which lead to safety risks to the analyst. Digital images have been used as an alternative to classic analytical methods, in which the color generated during a colorimetric reaction is associated with the variation in the concentration of analyte. Analyses that were previously restricted to equipment for laboratory use such as spectrophotometers, were carried out quickly, with lower cost and waste generation. Moreover, field analysis was feasible in such way. An analytical method based on the use of digital images has been proposed for the determination of the total sugar content of soft drinks. Rapidity, ease-to-use, portability, reduction of energy consumption and reagents and waste generation were considered. The images were captured with an external USB camera that can be coupled to any smartphone. The camera was inserted in a 3D-printed case and picture were taken directly from the flasks used for the colorimetric reactions. The images were obtained before and after the centrifugation step. Experimental parameters such as reaction time, total solution volume and lighting were evaluated. Compared with the official method (AOAC 923.09, Lane-Eynon titration), the proposed methods presented agreement from 95.3 to 108.7% with the official method. Hundreds of samples can be analyzed in one hour. The use of a chemical greenness index for evaluating the characteristics of the proposed method, was applied in this study, showing the reduction of energy expenditure by 5.5 times and 78 times less waste volume than the AOAC method.